Information Literacy Competencies as Correlates of Electronic Information Resources Utilization by Undergraduate Students in Obafemi Awolowo University, Ile – Ife, Osun State, Nigeria - Oyedapo, R. O.; Shabi, I. N.; Bamise, O. F. (MiddleBelt Journal of Library and Information Science, 2014)
The paper examines the information literacy competencies correlates of electronic information resources utilization by undergraduate students in Obafemi Awolowo University, Ile-Ife, Osun-State, Nigeria. Survey research design was used self administered questionnaire was used to collect data for the study. There are thirteen faculties in the university; sample size was determined by using multi-stage random sampling. A total number of 400 copies of the questionnaire were administered, 380 were properly filled and analyzed giving a response rate at 95% and 5% drop out rate. The findings of the study showed that a greater percentage of the respondents possess information literacy competency, and revealed that e-resources were readily available. However, availability does not mean utilization, Electronic resources in the library were underutilized by undergraduate students in O.A.U. The underutilization could be due to lack of awareness on the part of respondents. The paper recommends, among other strategies marketing of e-resources effectively to create awareness to the institutions community.